Estudo do ciclo diário da Camada Limite Planetária durante a estação chuvosa da Amazônia (GOAmazon 2014/15) - Carneiro, Rayonil Gomes (2018)
In the present study, the evolution the diurnal cycle of planetary boundary layer in the wet season at Amazon region during a period of intense observations carried out in the GOAmazon Project 2014/2015 (Green Ocean Amazon).The analysis includes radiosonde and remote sensing data. In general case, the results of the daily cycle in the wet season indicate a Nocturnal boundary layer with a small oscillation in its depth and with a tardy erosion. The convective boundary layer did not present great depth, responding to the low values of sensible heat of the wet season. A comparison between the different techniques(in situ observations and remote sensing)  for estimating the planetary boundary layer is also presented.